Evaluation of osseointegration of plasma treated polyaryletherketone maxillofacial implants - D S Abdullah Al Maruf; Jiongyu Ren; Kai Cheng; Hai Xin; Will Lewin; Edmund Pickering; Hedi Verena Kruse; David Leinkram; Krishnan Parthasarathi; Innes Wise; Benjamin Filippi; Stephen Beirne; et al. (Scientific Reports)
Abstract Osseointegration is a crucial property of biomaterials used for bone defect repair. While titanium is the gold standard in craniofacial surgeries, various polymeric biomaterials are being explored as alternatives. However, polymeric materials can be bioinert, hindering integration with surrounding tissues. In this investigation, plasma ion immersion implantation (PIII)-treated polyether ether ketone (PEEK) and polyether ketone (PEK) implants were assessed in a sheep maxilla and mandible model. Defects were filled with PIII-treated PEEK and PEK implants, produced through fused filament fabrication (FFF) and selective laser sintering (SLS), respectively. Positive controls were grade 23 titanium implants via selective laser melting, while untreated PEEK implants served as negative controls. Surface analyses using scanning electron microscopy and atomic force microscopy revealed favorable properties. Osseointegration was qualitatively and quantitatively assessed at 8-, 10-, and 12-weeks post-implantation, showing significantly improved outcomes for both PIII-treated PEEK and PEK implants compared to untreated controls. The study suggests PIII treatment enhances FFF-printed PEEK’s osseointegration, and PIII-treated SLS-printed PEK achieves comparable osseointegration to 3D printed titanium. These findings underscore surface modification strategies’ potential for polymeric biomaterials, offering insights into developing alternative implant materials for craniofacial surgeries, with enhanced biocompatibility and osseointegration capabilities for improved clinical outcomes.